ANALISIS KINERJA PELAYANAN ADMINISTRASI KEPENDUDUKAN JEMPUT BOLA PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SEMARANG - Dyah Ajeng Oktavia Pramesti; Kushandajani Kushandajani (Journal of Politic and Government Studies, 2026)
Civil service administration are a vital public service for ensuring that citizens’roghts are upheld. However, there are still people who face limited access to these services due to geographical conditions, advanced age, disabilities, or a lack of knowledge regarding population administration. To address these issues, the Semarang Regency Population and Civil Registration Office launched the Outreach Population Administration Service Program. This study aims to analyze the performance of the outreach population administration service during the 2024–2025 period and to identify the factors that support and hinder its implementation. This study employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation. Data analysis is conducted using Agus Dwiyanto’s service performance theory, which encompasses productivity, service quality, responsiveness, responsibility, and accountability. Research findings indicate that outreach services have successfully improved public access to civil registration services, particularly for vulnerable groups. Service performance was rated as good across all indicators, as evidenced by ease of access, satisfactory service quality, adherence to procedures, and transparent, free-of-charge services. Nevertheless, the program’s implementation still faces challenges, including limited human resources, insufficient outreach, the vast service area, and internet connectivity issues. Therefore, strengthened coordination, increased outreach, and optimized resource allocation are necessary to continuously improve service quality.